Indonesian Rheumatology Association (IRA) Recommendations for Diagnosis andManagement of Glucocorticoid-induced Osteoporosis - Bagus Putu Putra Suryana (Indonesian Rheumatology Associantion, 2022)
Background: Patients receiving long-term glucocorticoid therapy are at riskof developing GIOP. However, until today, there is still no guideline thatspecifically explains how to diagnose and manage GIOP patients inIndonesia. Methods: 10 selected rheumatologists from the IndonesianRheumatologist Association (IRA) made recommendations based on keyquestions formed by a steering committee from IRA. These recommendation materials were taken from several online databases such as Pubmed, Science Direct, and Cochrane. Level of evidence and grades of recommendation were then assigned, and every member of the panelist team will assign a score for the level of agreement. Results: A total of 17 recommendations regarding screening, prevention, diagnosis, therapy, and monitoring for GIOP weremade. Conclusion: These recommendations can be used for adult patientsreceiving long-term glucocorticoids with or at risk of developing GIOP. Theprevention measure, diagnostic, therapy, and monitoring algorithm in thisrecommendation are all created with the consideration of Indonesia’s clinical setting, facility, and drug availability.